2017
DOI: 10.1039/c7cp03770h
|View full text |Cite
|
Sign up to set email alerts
|

New insights into single-compound and binary adsorption of copper and lead ions on a treated sea mango shell: experimental and theoretical studies

Abstract: Herein, adsorption isotherms of Pb(II) and Cu(II) ions on treated sea mango fruit in both single-compound and binary systems were experimentally realized at different temperatures in the range of 30-50 1C.Experimental results show that adsorption of Pb(II) was more as compared to that of Cu(II) ions; however, for both ions, a significant reduction in the adsorption capacity was observed in the binary system as compared to that in the single-compound systems. Moreover, under all the investigated conditions, ads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 84 publications
(24 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…In singlecompound systems, the adsorption capacity of Pb (II) is higher than Hg (II) and for all the investigated temperatures. According to the literature, this difference could be explained by the physicochemical properties of adsorbates and adsorbent [26] and by differences in the interaction energies between the adsorbates and the adsorbent surface [14,15]. Furthermore, the adsorption of Hg (II) was significantly influenced by the presence of Pb (II) in binary systems.…”
Section: Pb(ii) and Hg(ii) Adsorption Isothermsmentioning
confidence: 99%
See 4 more Smart Citations
“…In singlecompound systems, the adsorption capacity of Pb (II) is higher than Hg (II) and for all the investigated temperatures. According to the literature, this difference could be explained by the physicochemical properties of adsorbates and adsorbent [26] and by differences in the interaction energies between the adsorbates and the adsorbent surface [14,15]. Furthermore, the adsorption of Hg (II) was significantly influenced by the presence of Pb (II) in binary systems.…”
Section: Pb(ii) and Hg(ii) Adsorption Isothermsmentioning
confidence: 99%
“…Analytically, the occupation of BAC receptor site by Pb (II) and Hg (II) heavy metals ions was illustrated by n and n i parameters defined as the number of ions captured by BAC receptor sites in singlecompound and binary system, respectively. However, even if these two parameters are steric, the studies of adsorption phenomena by statistical physics models [14,15] demonstrated that these parameters play an important role in explaining the adsorption mechanism but they are not dominant.…”
Section: Pb(ii) and Hg(ii) Adsorption Isothermsmentioning
confidence: 99%
See 3 more Smart Citations